KONTESTASI WACANA GOLPUT PADA MEDIA ISLAM MENJELANG PEMILU 2009 Analisis Praktik Kewacanaan pada Majalah Sabili dan Risalah Mujahidin Pasca Fatwa Haram Golput Majelis Ulama Indonesia - Denison Wicaksono * (Dimensia: Jurnal Kajian Sosiologi, 2011)
Towards the 2009 National Election of Indonesia, the discourse of the Non-voters or Golongan Putih (often called “Golput”) became hot issues in Indonesian mass media. It was then became debate among groups when the Indonesian Ulama Council (MUI) released a fatwa that being non voters is Haram (unlawful).  This Fatwa caused controversy among Muslims themselves, since there were support groups and opposed groups in responding this fatwa. This controversy was also accommodated by Islamic media. They have opportunities to construct a discourse through the text which have several tendencies. This study is intended to see and to map out the 2 (two) Islamic medias, Sabili and Risalah Mujahidin in constructing a text after the release of fatwa. Kata Kunci: Golput, media Islam, praktik kewacanaan